Neurovascular Complications of Iatrogenic Fusarium solani Meningitis - Strong, Nora; Meeks, Grant; Sheth, Sunil A.; McCullough, Louise; Villalba, Julian A.; Tan, Chunfeng; Barreto, Andrew; Wanger, Audrey; McDonald, Michelle; Kan, Peter; Shaltoni, Hashem; Campo Maldonado, Jose; et al. (The New England journal of medicine, 2024)
A multinational outbreak of nosocomial fusarium meningitis occurred among immunocompetent patients who had undergone surgery with epidural anesthesia in Mexico. The pathogen involved had a high predilection for the brain stem and vertebrobasilar arterial system and was associated with high mortality from vessel injury. Effective treatment options remain limited; in vitro susceptibility testing of the organism suggested that it is resistant to all currently approved antifungal medications in the United States. To highlight the severe complications associated with fusarium infection acquired in this manner, we report data, clinical courses, and outcomes from 13 patients in the outbreak who presented with symptoms after a median delay of 39 days. An outbreak of iatrogenic Fusarium solani meningitis occurred in early 2023 in association with epidural anesthesia in Mexico. Descriptions of 13 cases and associated management are presented.